Mirror affect : seeing self, observing others in contemporary art - Albu, Cristina (University of Minnesota Press, 2016)
For decades, contemporary artworks with reflective properties have stimulated public forms of spectatorship. According to Cristina Albu, these artworks, which can include elements such as mirrors, live video feedback, or sensors, draw attention to affective interdependence and mechanisms of social control. In "Mirror Affect", Albu provides a historical account of mirroring processes in contemporary art and offers insight into the phenomenological and sociopolitical concerns that have inspired artists to stage processes of affective, perceptual, and behavioral mirroring between art viewers. Beginning with the 1960s, Albu charts the rise of interpersonal modes of art spectatorship. She reveals contemporary artists? strategic use of reflective and responsive interfaces to instill doubt in visual representation and appeal to active scrutiny of the changing social dynamics. She suggests that the mirroring processes envisioned by contemporary artists such as Joan Jonas, Dan Graham, Lynn Hershman Leeson, Olafur Eliasson, and Rafael Lozano-Hemmer trigger visual disjunctions to upset narcissistic inclinations. They invite viewers to see themselves in relation to others and to ponder their role within complex social systems